Human Relations Management Maturity Model in the Teal Organization - Selected Issues - Joanna IWKO; Aneta PISARSKA (Communications of International Proceedings, 2020)
Nowadays, in the era of a great challenge in managing organizations, the model of teal organizations described by F. Laloux is becoming more and more popular. Many organizations are considering entering this way, and those that are already following it ask themselves at what stage are they "on the way to teal". The research problem is the attempt to answer the question: what are the maturity levels of the organization "on the way to teal" in the area of human relations? What characterizes a mature teal organization in the field of human relations? The aim of the article is to develop the initial concept of Human Relations Management Maturity Model in a teal organization. The research methods used in the study include critical analysis of the subject literature and logical reasoning.
Keywords: Maturity Model; Teal Organization; Human Relations; Recruiting and Selection